2003
DOI: 10.2337/diacare.26.12.3320
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Insulin Resistance by Simple Quantitative Methods in Subjects With Normal Glucose Metabolism

Abstract: OBJECTIVE -To identify a reliable yet simple indirect method for detection of insulin resistance (IR).RESEARCH DESIGN AND METHODS -A total of 65 subjects (44 men and 21 women aged 30 -60 years) were selected by a simple random sampling method. Inclusion criteria were voluntary participation from staff and hospital personnel, absence of abnormal glucose tolerance, and normal results of lipid profile and basic blood chemistry. A blood sample was taken after a 12-h overnight fast to determine plasma lipid, glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
301
4
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 417 publications
(323 citation statements)
references
References 29 publications
12
301
4
6
Order By: Relevance
“…20 and a HOMA-IR value p1.5 was considered indicative of normal insulin sensitivity. 21 A blood sample for measurement of adiponectin was collected. Plasma samples were immediately separated and stored frozen at À80 1C until measurement.…”
Section: Patientsmentioning
confidence: 99%
“…20 and a HOMA-IR value p1.5 was considered indicative of normal insulin sensitivity. 21 A blood sample for measurement of adiponectin was collected. Plasma samples were immediately separated and stored frozen at À80 1C until measurement.…”
Section: Patientsmentioning
confidence: 99%
“…Women were classified as being insulin resistant (IR group) or not insulin resistant (non-IR group) in accordance with defined cutoff points for HOMA-IR R2.5 (25,26), QUICKI %0.33 (26,27), and ISI %5 (20,24).…”
Section: ðLogðfiþðmu=mlþclogðfgþðmg=dlþþmentioning
confidence: 99%
“…Therefore, there remains a need for a simple IR test for routine screening, prospective studies, risk assessment, and therapeutic monitoring. 21,22 We reported a nontargeted metabolomics study using fasting plasma samples obtained from a healthy, nondiabetic population [Relationship between Insulin Sensitivity and Cardiovascular Disease (RISC) Study], searching for novel biomarkers of insulin sensitivity. 23 A number of small molecule metabolites were identified that correlated with the M values derived from the hyperinsulinemic euglycemic clamp.…”
Section: Introductionmentioning
confidence: 99%